2014
DOI: 10.1073/pnas.1419240111
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of long-range INS promoter interactions reveals a role for calcium-activated chloride channel ANO1 in insulin secretion

Abstract: We used circular chromatin conformation capture (4C) to identify a physical contact in human pancreatic islets between the region near the insulin (INS) promoter and the ANO1 gene, lying 68 Mb away on human chromosome 11, which encodes a Ca 2+ -dependent chloride ion channel. In response to glucose, this contact was strengthened and ANO1 expression increased, whereas inhibition of INS gene transcription by INS promoter targeting siRNA decreased ANO1 expression, revealing a regulatory effect of INS promoter on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…The increased glucose tolerance in TM LKO mice seems to contrast with the observations in TMEM16A global knockdown mice, in which a more severe glucose intolerance, due to deficiency of insulin secretion at the early stage of HFD (5 weeks) was reported. [ 22 ] An in vitro study further suggested that TMEM16A is required for glucose‐induced insulin secretion in β cells. [ 21 ] Two factors may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased glucose tolerance in TM LKO mice seems to contrast with the observations in TMEM16A global knockdown mice, in which a more severe glucose intolerance, due to deficiency of insulin secretion at the early stage of HFD (5 weeks) was reported. [ 22 ] An in vitro study further suggested that TMEM16A is required for glucose‐induced insulin secretion in β cells. [ 21 ] Two factors may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17,19 ] Additionally, selective renal knockout of TMEM16A was associated with a mild proteinuric phenotype. [ 20 ] TMEM16A was also involved in mediating glucose‐stimulated insulin secretion in islet β cells, [ 21,22 ] indicating that TMEM16A may also play a role in metabolic syndromes. Although the existence of CaCC in hepatocytes has been demonstrated, [ 23 ] the functional role of TMEM16A/CaCC in the liver is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Long-range interchromosomal and intrachromosomal interactions through chromosomal looping and transcription factories are known to be involved in the transcriptional coregulation of functionally related genes in a cell type-specific manner (Schoenfelder et al 2010;Papantonis et al 2012). For example, insulin expression and calcium signaling have been shown to be coupled through a longrange chromosomal interaction that spans >65 Mb (Xu et al 2014). lncRNAs have also been implicated in higher-order gene regulation through chromatin organization, and there is evidence of lncRNAs being highly enriched at transcription "factories" (Caudron-Herger et al 2015).…”
Section: Endocrine Development Is Affected In βLinc1mentioning
confidence: 99%
“…Once exposed to permeant anions, the Ca 2+ dependency of CaCCs will be altered (Qu & Hartzell, 2000;Xiao et al, 2011), suggesting that interactions of CaCCs with different anions can be coupled with calcium-sensing, voltage-sensing, and the gating kinetics of the channel. In comparison to Cl − , bulkier anions, such as NO 3 − , I − , and Br − , are preferred to cross the membrane (Rock, Futtner, & Harfe, 2008); gastrointestinal motility (Hwang et al, 2009); pain sensation (Cho & Oh, 2013;Huang et al, 2013;Takayama, Uta, Furue, & Tominaga, 2015); salivary gland secretion (Romanenko et al, 2010); airway epithelial secretion (Huang et al, 2009(Huang et al, , 2013; luminal pH regulation (Han Y, Shewan AM, & Thorn, 2016); insulin secretion (Crutzen et al, 2016;Edlund, Esguerra, Wendt, Flodstrom-Tullberg, & Eliasson, 2014;Xu et al, 2014); intestinal secretion and contraction (Namkung et al, 2010;Namkung, Phuan, et al, 2011;Namkung, Yao, et al, 2011); primary ciliogenesis (Ruppersburg & Hartzell, 2014); arterial myogenic response (Bulley et al, 2012); cerebral vasoconstriction (Li et al, 2011; pain and itch response (Liu, Cao, et al, 2015;Liu et al, 2010Liu et al, , 2016Liu, Liu, et al, 2015); airway smooth muscle contraction (Danielsson et al, 2015); thyrocyte iodide secretion (Twyffels et al, 2014); mucociliary clearance (Zhang et al, 2014Sondo, Caci, & Galietta, 2014); sweat secretion (Ertongur-Fauth, Hochheimer, Buescher, Rapprich, & Krohn, 2014); proinflammatory cytokine secretion inhibition (Veit et al, 2012); cancer cell proliferation and migration (Britschgi et al, 2013;Duvvuri et al, 2012;Guan et al, 2016;Jia et al, 2015;…”
Section: Biophysical Properties Of Caccsmentioning
confidence: 99%